Quantitative evaluation of trunk muscle strength in wheelchair basketball players - Sileno da Silva Santos; Angélica Castilho Alonso; Júlia Maria D'Andréa Greve (Universidade Estadual Paulista (UNESP), 2016)
Abstract Trunk muscle strength affects trunk controlling playing an important role in performance and to define the classes of wheelchair basketball players. Trunk control capacity differs among players and quantitative assessments of trunk muscle strength have not been investigated. The aim of this study was to identify and correlate quantitative measures of trunk muscle strength with the wheelchair basketball players' classification. Forty-two male wheelchair basketball players with spinal cord injury, amputation, post-poliomyelitis sequelae, and cerebral palsy had their trunk extension and flexion strength evaluated with isokinetic dynamometer. The classes 1.0, 2.0, 3.0, and 4.0 were considered for statistical analysis. Comparison of trunk muscle strength differed significantly between classes: 1.0 and 3.0; 1.0 and 4.0; 2.0 and 3.0; and 2.0 and 4.0. High correlation was found between the trunk muscle strength and players' classes. The findings of the present study showed a strong correlation of trunk muscle strength and wheelchair basketball classes being able to distinguish players in their classes. However, this quantitative method of evaluation of the trunk muscle strength cannot be solely used to make a decision on the full trunk control.